Pengaruh Ukuran Perusahaan, Profitabilitas, Ukuran Kap, Subsidiaries, Dan Komite Audit Terhadap Audit Delay (Studi Empiriris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Ramadhani, Jessica, Drs. Muhammad Abdul Aris, M.Si (2017)
The purpose of this research is to know are size of company, profitability, size of public accountant firms, and audit committee constitute of factors which influence of the audit delay at manufacturing companies registered in Indonesian Stock Exchange. The population is manufacturing company listed in Indonesian Stock Exchange in 2013 to 2015. Sampling technique employed is Purposive Sampling with the total sample of 77 companies. Analytical technique used in this research in analysis of multiple linier regression. The result shows size of company, size of public accountant firms, and audit committee is constitute of factors which influence of audit delay, while profitability and subsidiaries aren't constitute of factors which influence of audit delay. Keywords: audit delay, size of company, profitability, size of public accountant firms, and audit committee.